STRUKTUR DAN KOMPOSISI JENIS BURUNG DI KEBUN RAYA MEGAWATI SOEKARNO PUTRI, KABUPATEN MINAHASA TENGGARA - Orlio H. Ampouw; Hard N. Pollo; Reynold P. Kainde (COCOS, 2021)
ABSTRACTThis study aims to make an inventory of bird species in the KRMSP area, and analyze changesin the structure and composition of its bird species. This research was conducted in September 2020 atMegawati Soekarno Putri Botanical Garden, Ratatotok, Southeast Minahasa, North Sulawesi. Themethod used in this research was the IPA method (Indice Ponctuels d'Abondance) with priorityobservation points in the reclamation areas of years 2000, 2001, 2002, 2003/2004 and 2006/2007. Thisresearch covered a total of 15 observation points in 5 reclaimed areas. Results observed 896 birdindividuals, divided into 26 families and 44 species. Results were analyzed using the Shannon-Wienerdiversity index, resulting in a diversity value of 2.92. Comparative analysis of bird speciescomposition from 2008, 2009 and 2020 showed an increase on bird species and families as well as asignificant decrease in the number of individual birds observed. Comparison of Shannon-Wienerdiversity indices in years 2008, 2009 and 2020 show a moderate diversity value across all years. Thediversity index value in 2020 (2.92) is lower than in 2008 (2.94).Keywords: botanical garden, birds, comparative data.